Heavy Metal Contamination of Sediments from an Exoreic African Great Lakes’ Shores (Port Bell, Lake Victoria), Uganda - Baguma, Gabson; Musasizi, Andrew; Twinomuhwezi, Hannington; Gonzaga, Allan; Nakiguli, Caroline K.; Onen, Patrick; Angiro, Christopher; Okwir, Augastine; Opio, Boniface; Otema, Thomas; Ocira, Daniel; Byaruhanga, Ivan; et al. (Pollutants, 2022)
LakeVictoria (L.Victoria) is the largest African tropical and freshwater lake, with one of the highest pollution levels, globally. It is shared among Uganda, Kenya and Tanzania, but it is drained only by the river Nile, the longest river in Africa. Though environmental studies have been conducted in the lake, investigations of the heavy metals (HMs) contamination of sediments from ﬁsh landing sites and ports on the Ugandan portion of L.Victoria are limited. In this study, sediments of an urban, industrial and ﬁsh landing site (Port Bell) on L. Victoria, Uganda was investigated to establish its HMs pollution levels and potential health risks to humans and ecosystems. Sediment samples were collected in triplicate (n = 9) from three different points of Port Bell, digested and analyzed using atomic absorption spectrometry for the presence of these HMs: copper (Cu), lead (Pb), cadmium (Cd) and chromium (Cr). The average daily dose through dermal contact and hazard quotient (HQ) were calculated to assess the health risk that is associated with dredging works (lake sand mining). Four geochemical enrichment indices: contamination factor (CF), geo-accumulation index (Igeo), pollution load index (PLI) and potential ecological risk (PERI) were used to quantify the contamination of the HMs in the sediments. The results showed that the mean HM content of the samples ranged from: 6.111±0.01 to 7.111±0.002 mg/kg for Cu; from 40.222±0.003 to 44.212±0.002 mg/kg for Pb; from 0.352±0.007 to 0.522±0.010 mg/kg for Cr; from 3.002±0.002 to 3.453±0.003 mg/kg for Cd. Health risk assessments indicated that there are no discernible non-carcinogenic health risks that could arise from the dredging works that are conducted in the study area as the indices were all below one. The contamination factors that were obtained suggest that Cd has reached a state of severe enrichment in the sediments (CF > 6). An assessment using Igeo established that the sediments were not contaminated with regards to Cu and Cr, but they exhibited low-to-median and median contamination with respect to Pb and Cd, respectively. Though the pollution load indices show that the contamination levels raise no serious concerns, the potential ecological risk indices show that there is considerable pollution of the Port Bell sediments, particularly with regard to Cd. Upon examination using multivariate statistical analyses, Cd and Cr showed a strong correlation which alluded to their introduction from anthropogenic sources. Based on the sedimentary HMs concentrations and the environmental indices that are employed in this study, it is recommended that the spatial variations in the concentrations of the HMs in water, sediments and biota should be monitored.
Keywords: Trace metals; Lake Victoria; Murchison bay; Hazard index; Geo-accumulation index